A Comparative Study of Rural Entrepreneurial Challenges: Towards Rural Economic Development and a Policy Framework - Agbenyegah, Albert Tchey (Journal of Economics and Behavioral Studies, 2019)
The primary purpose of this rural study was to compare the challenges that impede successful operations of entrepreneurial activities and small businesses. Through quantitative design, a seven-point Likert-scale questionnaire was utilized to gather primary data. Two sampling techniques, namely simple random and purposive, were applied to select the research participants. Based on a Likert spectrum, 267 questionnaires were administered to SME owners by the researcher, assisted by two research trainees. These questionnaires were ranked from (1) strongly disagree to (7) strongly agree. Two main questions, which provided guidance to this study, were certified reliable by the Cronbach alpha coefficient of 0.768 and 0.976. Data analysis was possible through the descriptive and inferential tools supported by the independent t-test, Pearson’s chi-square test, and cross-tabulation. The final outcomes demonstrate higher levels of challenges in the Frances Baard (FB) District than in the John Taolo Gaetsewe (JTG) District. This implies that owner-managers of small businesses in the FB District experienced more challenges in operating their businesses. The study recommends SME Policy Framework (SPF) training and intensifying the existing processes of monitoring after training to justify the owner-managers’ moral commitments.